English for Specific Purpose (ESP) Teaching Design Based on Accounting Students Needs Analysis - Angga Prasongko (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Kadiri, 2023)
The Asean Economic Community (AEC) and the World Trade Organization (WTO) are challenges that need to be faced by higher education administrators. Higher education graduates are required to have the ability for facing the global competition. One of the skills that needs to be mastered is communication in using international languages. It must provide by study program to deliver in English teaching program. Currently, lecturers' perspectives serve to shape the teaching of English for Specific Purposes (ESP). Learning Needs Analysis is supposed to create the basis of ESP English instruction. Based on that problem, research was carried out to conduct a learning needs analysis for ESP English learners to determine appropriate learning design recommendations. This research uses a qualitative approach with interviews, observation, and closed-ended questionnaires as data collection techniques. This research shows the most appropriate English learning design for accounting students is to focus on speaking skill. It should be applied in active classes activity; students centered and the role of the lecturer as a facilitator. These elements aim to improve the self-quality of students and prepare them for future career.